HUKUM KELUARGA DAN PERKAWINAN MERUPAKAN DASAR KEPASTIAN DAN KENYAMANAN DALAM KELUARGA - I Gusti Agung Jaya Suryawan (PARIKSA: Jurnal Hukum Agama Hindu, 2018)
Marriage is a very important institution in society. The existence of this institution is to legalize legal relations between a man and a woman. Therefore, some experts view and give a very important meaning to the institution called marriage. Asser, Scholten, Pitlo, Petit, Melis, and Wiarda provide the definition that marriage is a fellowship between a man and a woman who is recognized by the state for eternal communion. The essence stated by these experts is that marriage is a legal institution, both because of what is inside it, or because of what is contained within it. Meanwhile, according to Soetojo Prawirohamidjojo stated that marriage is a life alliance between a man and woman who is formally confirmed by the Law (juridis) and mostly religious. Another opinion was conveyed by Subekti in his book Principles of Civil Law which said that marriage is a legitimate relationship between a man and a woman for a long time. The basics of marriage are formed by the natural elements of life itself; biological needs and functions, reduce, need for affection and brotherhood, nurture children born from the marriage and educate those children to become perfect members of society (volwaardig). Certain forms of marriage are not given by nature; various forms of marriage function as institutions (institutions).